Self-medication as an Initial Treatment and its Associated Complications in Ophthalmic Patients at Al-Khidmat Teaching Hospital, Mansoorah, Lahore, Pakistan: Doi: 10.36351/pjo.v40i3.1797 - Tariq, Farah; Amir, Muhammad Mateen; Mehmood, Zahid; Hashmi, Anwar ul Haq (Pakistan Journal of Ophthalmology, 2024)
Purpose: To identify self-medications used by patients as initial treatment for various eye problems and to analyze associated complications. Study Design: Cross sectional. Place and Duration of Study: Al-Khidmat teaching hospital, (University of Lahore) from October 2021 to September 2022. Method: This study included 117 patients using traditional eye medications (TEM) and over the counter (OTC) ophthalmic drugs before presenting in ophthalmic outdoor. A semi structured questionnaire was used as a tool to collect the data. All patients aged 18 years and above were directly questioned. For patients below 18 years, responses were collected from the patients themselves when possible; otherwise, the accompanying parent provided the information. Age, gender, educational status and area of residence were recorded. The symptoms compelling the use of TEM/OTC or both, the source and type of medication, diagnosis and any complications that resulted due to self-medication were documented. Complete ocular examination was done. MS Excel was used to record and analyze data. Results: There were 48% males and 52% females. Rosewater was the most frequently used TEM by 54.7%. Steroids-antibiotic combination eyedrops/ointments were used by 31.6%. Symptoms for which self-medication was done, were redness (64.1%), watering (35.9%), itching (32.5%) and discharge (26.5%). Symptoms did not improve in 54.7%, 26.5% required ophthalmic consultation and only 18.8% had temporary relief. Twelve percent developed complications. Conclusion: Self-medication with TEM or OTC drugs should be discouraged as these can cause detrimental effects on eyes.